Monetary and financial integration in East Asia the relevance of European experience - d; Wyplosz, Charles (Oxford : Oxford University Press, 2010)
This volume looks at East Asia's monetary and financial integration from both Asian and European perspectives. It analyses the Euro area's framework for monetary policy implementation, introduced in 1999, and reviews the efforts to foster regional monetary and financial integration and relates them to Europe's own evolution.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Monetary policy -- Asia; Asia -- Economic integration; Asia -- Economic conditions -- 1945-; Europe -- Economic integration